Design considerations for retirement savings and retirement income products - Lakshman, Alles (Palgrave Macmillan Ltd., 2011)
In the backdrop of a world with an ageing population and increasing life expectancy, the impact of the global financial crisis on the values of pension and superannuation funds has underscored the vulnerability of the wealth pool of retirees and their well-being during retirement. In light of this, it is important to examine how the design and delivery of retirement savings and income products can address these vulnerabilities. The purpose of this article is to review and evaluate the factors that need to be considered and the features that need to be incorporated in designing and developing retirement savings and retirement income products to address the concerns of investors, both in the accumulation and draw down phases of retirement investment management.